ANALYSIS OF LECTURERS’ ATTITUDE TOWARDS INTEGRATION OF ICTS IN TEACHING UNIVERSITY STUDENTS IN YOBE STATE, NIGERIA - Muraina Kamilu Olanrewaju; Saleh Musa .; Zahrau Muhammad Kabir (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The study examines the lecturers’ attitude towards integration of ICTs in teaching University students in Yobe State, Nigeria. Descriptive research design of ex-post facto type was used with 125 participants drawn for the study. The respondents were measure with standardize instrument with reliability coefficient of 0.75 using Cronbach Alpha and the data collected was analysed using mean, standard deviation (SD) and t-test 0.05 level of confidence. The finding revealed that attitude of lecturers towards integration of ICTs in teaching undergraduate students was negative; level of lecturers’ competency in the use of ICT facilities was low and there was statistically significant difference between male and female lecturers attitude in favour of male lecturers. The study recommends the following based on the findings of study: There is a need for the Government, National University Commission (NUC) and other Education stakeholders to respond positively and provide enough ICT infrastructures in all University across the country so as to encourage lecturers to utilize them in their teaching.